An Totoóng Hélang And Blog In The Time of Corona - Manaog, Niño Saavedra (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
Two years through the pandemic, contradicting stories on the Coronavirus— but also doubts about its vaccines—persist, serving only to obfuscate. In the midst of all these, one wonders what illness—or which disease—is more debilitating. After months of lockdown and isolation, people not only became sad and bad; they were mad. This wordplay ought to be spoken in full effect—if only to capture all these emotions.